Existence of Mild Solutions for Hilfer Fractional Evolution Equations with Almost Sectorial Operators - Mian Zhou; Chengfu Li; Yong Zhou (Axioms, 2022)
In this paper, we obtain new sufficient conditions of the existence of mild solutions for Hilfer fractional evolution equations in the cases that the semigroup associated with an almost sectorial operator is compact as well as noncompact. Our results improve and extend some recent results in references.